2012
DOI: 10.12660/rbfin.v10n1.2012.2654
|View full text |Cite
|
Sign up to set email alerts
|

Planos de Opções de Compra de Ações e o Valor das Companhias Brasileiras

Abstract: This work investigates the effects of Employee Stock Options Plans (ESOP) on the value of companies in the Brazilian Stock Exchange (BM&FBOVESPA). An ESOP is a mechanism of variable compensation, generally offered to executives, having the alignment of interests between managers and shareholders as one of its goals. To achieve this purpose, a panel data analysis was used in order to try m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The independent variables, the object of this study, are detailed below: Stock option plan = binary variable that aims to show whether the company has the plan or not. If it does not have a plan, the variable will be represented by 0; otherwise, it takes value 1.It is expected that there is a negative correlation with the dependent variable, that is, companies that adopt stock options distribute fewer dividends (de Moura, Padilha, & Silva, 2016; Perobelli, Lopes, & Silveira, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…The independent variables, the object of this study, are detailed below: Stock option plan = binary variable that aims to show whether the company has the plan or not. If it does not have a plan, the variable will be represented by 0; otherwise, it takes value 1.It is expected that there is a negative correlation with the dependent variable, that is, companies that adopt stock options distribute fewer dividends (de Moura, Padilha, & Silva, 2016; Perobelli, Lopes, & Silveira, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…The little evidence available is conflicting. On the one hand, it was found that firms that pay their executives more do not have a higher market value or better performance (Carvalhal-da-Silva and Chien, 2013) whereas other results indicate that the share prices of firms that adopt stock options increase (Perobelli et al , 2012). The relationship is either positive or non-existent, but it does not seem to be negative.…”
Section: Review Of the Literature And Research Questionsmentioning
confidence: 99%
“…Ainda sob o prisma contábil, há estudos evidenciando que empresas que concedem ESO tendem a apresentar resultados melhores em termos de valorização da ação do que aquelas que não instituíram planos nesse sentido ou o fizeram há menos tempo (Perobelli et al, 2012); o impacto negativo das despesas com ESO sobre a performance das empresas (Botosan & Plumlee, 2001); e a migração das empresas para estruturas de PBA envolvendo a entrega de recursos financeiros aos beneficiários, possivelmente por haver, nesse modelo, maior espaço para o gerenciamento de resultados (Alhaj Ismail et al, 2019).…”
Section: Justificativa E Contribuiçõesunclassified